Knowledge, attitudes and quality of life of caregivers towards asthma in their children: a Nigerian perspective (Journal of Health Sciences, 2020)
Introduction: The burden of uncontrolled asthma is high and caregivers can offer support in the management of asthma. Asthma is one of the most common chronic diseases in children. The objective of this study was to assess the knowledge, attitudes, and quality of life (QoL) of caregivers toward asthma in their children.Methods: This cross-sectional study was conducted in the Paediatric Respiratory Unit of the University of Nigeria Teaching Hospital, Ituku-Ozalla, Enugu State (July 2017-September 2017). We utilized a 46-item questionnaire comprising knowledge and attitude domains and the 13-item Pediatric Asthma Caregiver’s QoL Questionnaire (PACQLQ). Data were analyzed using the IBM SPSS Version 25.0. Statistical significance was set at p < 0.05.Results: Fifty-one caregivers participated in the study. More than half (n = 36, 70.6%) of the caregivers were 40 years old and above, female (n = 37, 72.5%), graduates from higher institutions (n = 33, 64.7%), and self-employed (n = 27, 52.9%). About a quarter (n = 13, 25.5%) had a family history of asthma and a similar proportion (n = 14, 27.5%) knew the three main symptoms of asthma.Conclusion: Less than half (n = 24, 47.1%) of the caregivers had good asthma knowledge. Dust (n = 35, 68.6%) and smoke (n = 31, 60.8%) were identified as the most common asthma triggers in their children. The majority of the caregivers (n = 41, 80.3%) agreed that most people can have well-controlled asthma without seeing a doctor regularly. Overall, less than half of the caregivers (n = 24, 47.1%) showed positive attitudes toward their children’s asthma. The overall score for the PACQLQ was 3.91 (0.98) which implied a poor QoL. The caregivers had both impaired activity and emotional function from managing asthma in their children. More female caregivers had better knowledge about asthma than their male counterparts (t = −3.178; df = 49; p = 0.003). Less than half of the caregivers had good asthma knowledge and positive attitudes toward asthma in their children. They had an impaired QoL from managing asthma in their children.